Prestressed cold-formed steel beams: concept and mechanical behaviour - Hadjipantelis,N; Gardner,L; Wadee,MA (Engineering Structures, 2018)
An innovative concept, whereby the load-carrying capacity and serviceability performance of cold-formed steel beams are enhanced by utilising prestressing techniques, is presented. The prestressing force is applied by means of a high-strength steel cable, which is housed at a location eccentric to the strong geometric axis within the bottom hollow flange of the cold-formed steel beam, inducing initial stresses in the beam that are opposite in sign to those introduced during the subsequent loading stage. As a consequence, the development of local instabilities during loading is delayed and thus the capacity of the beam is enhanced. Furthermore, the pre-camber induced during prestressing, as well as the contribution of the cable to the bending stiffness of the system, decrease the overall vertical deflections of the beam. The conceptual development of prestressed cold-formed steel beams and a study investigating the potential benefits are presented. The mechanical behaviour of the proposed beams in both the prestressing and imposed loading stages is described in terms of analytical expressions, while failure criteria for the design of the cold-formed steel beam and the cable are also developed by employing interaction equations in conjunction with the Direct Strength Method. Geometrically and materially nonlinear finite element analysis with imperfections is employed to simulate the behaviour of the proposed beams. Sample numerical results are presented and compared with the developed analytical expressions and failure criteria, demonstrating the substantial enhancement in moment capacity and serviceability performance offered by these beams.